Green synthesis of curcumin functionalized Au nanoparticles by visible light photo-reduction - Kumar S.; Kuntail J.; Sahu D.K.; Yadav V.S.; Sinha I. (My University, 2025)
The present study reports the green synthesis of gold nanoparticles by reducing auric chloride (HAuCl4) with alkaline curcumin under visible light irradiation. Curcumin is a conjugated molecule with a visible light HOMO–LUMO gap. Given this, white and red light (LED sources) were irradiated on aqueous solutions of curcumin and HAuCl4. Under visible light irradiation, curcumin got photo-excited, and the electrons excited to the LUMO of the molecule reduced HAuCl4 to Au nanoparticles (AuNPs). Since curcumin can also be a mild reducing agent in the dark, it reduced HAuCl4 to Au nanoparticles under these conditions. Subjecting the reaction mixture to different light irradiation conditions led to synthesizing six variations of curcumin-stabilized AuNP dispersions (c-AuNPs). Varying light wavelengths altered HAuCl4 to AuNPs reduction kinetics and, thereby, the nanostructure of the latter. The size and shapes of c-AuNPs were inspected from transmission electron microscopy (TEM) analysis. The prepared AuNPs dispersions were further used as catalysts for reducing 4-nitrophenol (PNP) to p-aminophenol (PAP), a model reaction. Different c-AuNPs dispersions catalyzed the PNP to PAP reduction reaction with varied activation energies and reaction rates. The catalytic activities of AuNPs are mainly affected by their activation energy. © 2023, Indian Association for the Cultivation of Science.